2006
DOI: 10.1186/1471-2458-6-82
|View full text |Cite
|
Sign up to set email alerts
|

An examination of knowledge, attitudes and practices related to lead exposure in South Western Nigeria

Abstract: Background: Lead is a highly toxic and pervasive metal. Chronic exposure to low levels is responsible for significant health effects, particularly in children. Prevention remains the best option for reducing childhood lead exposure, however the knowledge, attitudes and practices to lead exposure in many developing countries is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…However, in the posttest and follow up phases their knowledge improved .This may be due to sufficient background from prior formal education in environmental health as in table. On the contrary, a study in South Western Nigeria by ( Adebamowo, Agbede &Sridhar 2006). it was found that there was limited awareness regarding these items and participants had little knowledge of the health effects of chronic low-dose lead exposure.…”
Section: Discussionmentioning
confidence: 97%
“…However, in the posttest and follow up phases their knowledge improved .This may be due to sufficient background from prior formal education in environmental health as in table. On the contrary, a study in South Western Nigeria by ( Adebamowo, Agbede &Sridhar 2006). it was found that there was limited awareness regarding these items and participants had little knowledge of the health effects of chronic low-dose lead exposure.…”
Section: Discussionmentioning
confidence: 97%
“…It is noted that most of the studies on lead exposure and blood pressure relationship have been done in developed countries. There is consequently a paucity of studies evaluating the role and contribution of lead exposure on elevated blood pressure and hypertension in countries like Nigeria, where lead exposure is considered to be prevalent and unregulated [37] [38] [39] [40] [41] and Occupational Diseases and Environmental Medicine This study which evaluated the relationship of blood lead and blood pressure among lead exposed workers established a significantly higher degree of lead exposure in the study subjects compared to controls as demonstrated by significantly higher mean BLL in study subjects compared to controls 50.3 ± 24.5 ug/dl vs. 41.40 ± 26.85 ug/dl. This finding is consistent with reports from other Nigerian studies reporting higher mean BLL in occupationally exposed populations compared to controls of 56.3 ± 0.95 ug/dl vs 30.47 ± 1.4 ug/dl [47], 48.09 ± 9.08 ug/dl vs 33.65 ± 10.09 ug/dl [48] and 46.0 ± 0.19 ug/dl vs 31.0 ± 0.10 ug/dl [38] respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of environmental and occupational lead exposure needs to be prioritized and made a public health issue in Nigeria especially in subjects engaged in risk occupations. In furtherance of this goal, efforts should be intensified to improve the low awareness and regulation of lead exposure and toxicity [41]; while the expected gains from the reduction of leaded gasoline use in the country [62], should be complemented by other strategies which include the reduction of the high level of lead in paint and pigment [63] [64] and other sources of lead exposure [65]. The risk from unregulated ore mining [40] and other artisanal occupational activities which promote lead exposure ought to be reduced through tougher environmental and occupational regulation of lead exposure in order to reduce the high burden and cost of lead exposure and toxicity in Nigeria, with its established impact on cardiovascular related diseases like hypertension [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few have knowledge of domestic sources of lead, such as paint, water, and soil. [3] Undue exposures to lead, particularly among transferred to the blood diluent reagent provided with the kits. Blood collection was done three times at 6-month intervals including the initial screening to monitor the BLLs.…”
Section: Sample Collectionmentioning
confidence: 99%